Delphinid systematics and biogeography with a focus on the current genus Lagenorhynchus: Multiple pathways for antitropical and trans-oceanic radiation - Banguera Hinestroza, Eulalia; Hayano, Azusa; Crespo, Enrique Alberto; Rus Hoelzel, A. (Molecular Phylogenetics and Evolution)
The six species currently classiﬁed within the genus Lagenorhynchus exhibit a pattern of antitropical distribution common among marine taxa. In spite of their morphological similarities they are now considered an artiﬁcial grouping, and include both recent and the oldest representatives of the Delphinidae radiation. They are, therefore, a good model for studying questions about the evolutionary processes that have driven dolphin speciation, dispersion and distribution. Here we used two different approaches. First we constructed a multigenic phylogeny with a minimum amount of missing data (based on 9 genes, 11,030 bp, using the 6 species of the genus and their closest relatives) to infer their relationships. Second, we built a supermatrix phylogeny (based on 33 species and 27 genes) to test the effect of taxon sampling on the phylogeny of the genus, to provide inference on biogeographic history, and provide inference on the main events shaping the dispersion and radiation of delphinids. Our analyses suggested an early evolutionary history of marine dolphins in the North Atlantic Ocean and revealed multiple pathways of migration and radiation, probably guided by paleoceanographic changes during the Miocene and Pliocene. L. acutus and L. albirostris likely shared a common ancestor that arose in the North Atlantic around the Mid- dle Miocene, predating the radiation of subfamilies Delphininae, Globicephalinae and Lissodelphininae. Fil: Banguera Hinestroza, Eulalia . University Of Durham; Reino Unido Fil: Hayano, Azusa . Kyoto University; Japón Fil: Crespo, Enrique Alberto. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Nacional Patagónico; Argentina Fil: Rus Hoelzel, A. University Of Durham; Reino Unido